Colitis A Practical Approach to Colon Biopsy Interpretation - Geboes, Karel; Nemolato, Sonia; Leo, Maria; Faa, Gavino; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This concise book explains how to analyze endoscopic mucosal biopsies of the colon obtained for diagnosis and follow up of colitis in general and  inflammatory bowel diseases (ulcerative colitis, Crohn’s disease and microscopic colitis) in particular. This is achieved by the presentation of basic lesions in multiple drawings together with an explanatory text and microscopic photographs. The description is completed by a review of various differential diagnostic issues and types of colitis. Colitis: A Practical Approach to Colon Biopsy Interpretation is aimed at general pathologists and pathologists in training and also gastroenterologists to help them understand how a precise diagnosis can be reached.
The Normal Biopsy: Mucosa And Submucosa -- The Endoscopic Biopsy -- Elementary Lesions Of Inflammation -- Dysplasia -- Infections -- Inflammatory Bowel Diseases -- Treatment Related Diseases -- Ischemic Colitis -- Diverticular Disease-Associated Colitis -- Eosinophilic Colitis -- Microscopic Colitis -- Drug-Induced Colitis -- Solitary Rectal Ulcer Syndrome -- The Role Of Biopsies In The Treatment Of Colitis: Scoring Of Disease Activity.
Keywords: Pathology; Gastroenterology .; Pathology; Gastroenterology